Third global ODA forum for sustainable agricultural development - International Livestock Research Institute (International Livestock Research Institute, 2019)
The third global ODA forum for sustainable agricultural development on inclusive growth and global partnership was held 13-15 May 2019 in Seoul, South Korea. The following ILRI researchers spoke at the conference: 1:07 Hung Nguyen, ILRI regional representative for East and Southeast Asia. 24:40 Delia Grace, ILRI program leader, Animal and Human Health. 50:52 Hu Suk Lee, ILRI scientist.